(untitled) (ADI Journal on Recent Innovation (AJRI), 2023)
Reaction and separation are the two most important processes in the chemical industry that significantly affect the overall energy and cost requirements. Therefore, the operation of integrated reactive separation in a single equipment, such as reactive distillation, potentially increases the chemical process efficiency remarkably. To achieve that advantage, it is vital to design an optimum reactive distillation configuration in the preliminary evaluation. This paper proposes structured data management that can be used to encounter an optimum reactive distillation design. The approach simplified and reduced the data necessity from thousands to dozens by applying a systematic data sorting for the simulation results obtained from the Aspen Plus simulator. Using a case study that is highly relevant to the real chemical processes, i.e., the metathesis of 2-pentene, this study showed that the rule of thumb for determining the optimum design of conventional distillation can be adapted for reactive distillation technology.